Development of polyclonal antibodies for detection of Monodon baculovirus (MBV) in Penaeus monodon - Penaranda, Ma. Michelle D. (Miagao, Iloilo University of the PHilippines in the Visayas, 2004)
Monodon baculovirus (MBV) is a prevalent viral disease in Penaeus monodon especially in the Philippines. Polyclonal antibodies (PAbs) against MBV were developed by immunization of rabbits with the purified virus. The antisera were then evaluated using indirect flourescence antibody test (IFAT), immunohistochemistry (IHC) and indirect enzymelinked immunosorbent assay (ELISA). Intense immunofluorescence was observed in impression smears and paraffin-embedded sections of MBV-infected P. monodon postlarvae (PL-15 to 20) but not in smears and/or sections infected with hepatopancreatic parvovirus (HPV) and white spot syndrome (WSSV). Similarly, immunohistochemical test on paraffin-embedded sections showed positive coloration (brownish red to rose red precipitate) in MBV-infected cells not found in sections infected with either HPV WSSV. Indirect Elisa test revealed that the rabbit PAbs could detect up to 4 ng (Rabbit 1) and 100 ng (Rabbit 2) of purified MBV. However, testing of crude shrimp homogenates (gills of WSSV-infected adult P. monodon, head portion of HPV - and MBV-infected PLs, and non-infected PLs) by indirect ELISA indicated highe level cross-reactions that can be attributed to the relatively low titers of the antisera and the presence of certain factors in the shrimp extracts that bibd non-specifically to the antibody. Overall, the PAbs developed in this study have potential application in the rapid, sensitive, specific, and inexpensive detection of MBV provided that further purification of the sera performed to further minimize background reactions. Also, with additional improvement in the immunoassay protocols, they can be used as a simple and reliable research tool for future studies of the virus.
Thesis (Master of Sciences in Biology)-- Miagao, Iloilo : University of the Philippines in the Visayas, April 2004.
Keywords: Monodon baculovirus